Effect of tannic acid modified bamboo fiber on the performance of soybean bio‐asphalt/styrene‐butadiene‐styrene modified asphalt. Issue 4 (11th February 2022) - Meng, Yongjun; Qin, Pengfei; Yaseen, Muhammad; Chen, Jing; Yan, Tianyi; Gan, Weixing; Lei, Jiechao; Li, Jing
Abstract: This study resolves the poor enhancement problem of high‐temperature performance and lower dissolution of styrene‐butadiene‐styrene (SBS) modified asphalt and soybean bio‐asphalt (SBA) (extracted from waste soybean oil) by tannic acid (TA) modified bamboo fiber (MBF). The rheological properties and microscopic morphologies of the modified asphalt and fibers were investigated by dynamic shear rheometer (DSR), multiple stress creep recovery (MSCR) tests, and Fourier transform infrared (FTIR) spectroscopy. The results showed that the rutting factor and deformation recovery rate of 3% MBF/3% SBS/SBA modified asphalt at 64°C increased by 78.4% and 31.99% as compared with those of 5% SBS modified asphalt. Further, the phenolic hydroxyl group of TA reacted with C═O groups in SBA to form a strong connection between BF and bio‐asphalt. Fluorescence microscopy analysis revealed that SBS solubilization and BF formed a uniform and stable network structure in the modified asphalt. This study provides a useful, greener, and cost‐effective strategy for the effective utilization of industrial waste (BF and waste soybean oil) by converting into advanced functional materials for highway and construction industries novel and hence can concomitantly decrease environmental pollution and enhance energy conservations. Abstract :